Mechanisms of resistance to radiation - (:unkn) unknown (Springer New York, 2013)
Radiotherapy is a very effective treatment for achieving local tumor control in breast cancer. However, intrinsic tumor cell radioresistance is a significant clinical problem that limits the results of the treatment. Chemotherapeutics that could specifically sensitize tumors to radiation would greatly increase the ability to deliver higher doses while limiting radiation damage to surrounding normal tissue, but efforts to develop clinically useful tumor radiosensitizers have had limited success. © Springer Science+Business Media New York 2013.